Data Immutability Challenges: A Security Analysis of Digital Archiving Systems - Senthilkumar, T.; Rajasekaran, S. (Journal of ISMAC, 2022)
This study examines how well ‘cloud computing’ and ‘digital archive resource management’ work in the present time and what advantages they provide. Additionally, it explains a novel approach to using cloud computing by means of blockchain with an appropriate technique for sharing and distributing digital archive contents. The combination of virtualization and cloud storage technologies results in a widely accessible dataset. Specifically, it demonstrates its high security, excellent scalability, and ideality for standardization. This article also investigates the feasibility of implementing the archival bond in a blockchain-based record-keeping infrastructure. To achieve this, it suggests a database backend that preserves the immutability of the blockchain while facilitating metadata updates and improved search capabilities.
Keywords: Archive information; security; big data; block chain; confidentiality management; digital archives